LEGAL PROBLEM SOLVING PENUMPUKAN PERKARA PIDANA DI INDONESIA MELALUI PENGADOPSIAN KONSEP PLEA BARGAINING GUNA MEWUJUDKAN PERADILAN PIDANA YANG EFEKTIF DAN EFISIEN - Ruchoyah Ruchoyah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2018)
The process of criminal justice system in Indonesia up to this time still becomes issues that have not been resolved, one of them is the stacking of the criminal justice system in Indonesia. The stacked problem of cases shows that the criminal justice system in Indonesia has been less effective and efficient so that until now a simple, quick and lightweight judicial process cannot be realized in the criminal justice system in Indonesia. This research gives a legal problem solving toward the stacked problems of criminal cases in Indonesia that are currently not able to solve, namely the implementation of plea bargaining system in the renewal of the criminal justice system in Indonesia by conducting comparative studies of the implementation of plea bargaining system in the criminal justice system in the United States. The results of this paper show that the urgency in the application of the plea bargaining system in Indonesia can be seen from several considerations:, philosophical, juridical, sociological and political laws. The conclusions and the recommendations from the author is that a plea bargaining system should be adopted in the renewal of the criminal justice system in Indonesia in order to realize an effective and efficient criminal justice. Keyword : Legal Problem Solving,Plea Bargaining, Cases.